Survey of library resources and services of land transport-related agencies in the Philippines with implications for the creation of Land Transportation Information Network (LATIN) - Opinaldo, Elsie I. (1997)
Presents the strengths and weaknesses of libraries and information centers' attached to land transport-related agencies in the Philippines in terms of resources such as collection, equipment, budget, personnel and their capability to join a networking or resource sharing program. The instrument used in data gathering was a structured questionnaire patterned after the studies of Akbar (1986), Lucas (1986) and Tantiongco (1996). One of the major findings is that information resources on transportation is so scarce especially on the four subject areas of specialization in the field, i.e. transportation planning, traffic engineering, transportation and traffic management, and traffic law enforcement. Only seven agencies have organized libraries, i.e., those of the National Center for Transport Studies (NCTS), National Economic and Development Authority (NEDA), Department of Transportation and Communications (DOTC), Department of Public Works and Highways-Main Office (DPWH-Main), Department of Environment and Natural Resources (DENR), Environmental Management Bureau (EMB), and Bureau of Research and Standards (BRS). NEDA has the biggest collection, which specializes on planning and economic development although its collection on transportaion is rather small. DOTC's collection focuses on all modes of transportation, but not as big as compared to NCTS. On the other hand, NCTS Library has the largest collection on transportation. The book holdings of these thirteen transport related libraries totalled 35,247 volumes. The bulk of these materials is at the NCTS Library. Periodicals are not evenly distributed in these institutions. DOTC has the biggest collection of periodicals/journals followed NCTS, NEDA, DENR, DPWH-Main, PMO-FS, BRS while LTO, EMB and PNP have the least number of collection.